The Socialization Activity “Sahabat Bumi: Anak Hebat Peduli Lingkungan” at SD Negeri Bukit Rawi 1, Kahayan Tengah District, Pulang Pisau Regency, Central Kalimantan - Intan Kumalasari; Aldi; Ahmad Riza; Amelinda; Asripho; Clara Helenika; Dea Siska Rolin; Nadia Anggiriani; Nadila Enggle Ria; Ropi Julio; Sasae; Silvi afrilia Zumarnis; Yumirara (PT Polstac Repositori Riset, 2026)
Background: arious problems are still frequently encountered, such as the accumulation of plastic waste, the habit of improper waste disposal, limited understanding of the separation between organic and inorganic waste, and a low level of awareness of the environmental impacts on public health. Contribution: The socialization activity ‘Sahabat Bumi: Anak Hebat Peduli Lingkungan’ is a community engagement program conducted by the K3 Team of the Faculty of Social and Political Sciences, University of Palangka Raya, Department of Government Studies, and implemented at SD Negeri Bukit Rawi 1. Method: The implementation of the activity was designed to enable students to understand basic environmental concepts, recognize environmental problems in their immediate surroundings, and practice environmentally friendly behavior in their daily lives Results: Overall, this activity demonstrated the effectiveness of collaboration between university students and the school in supporting the character development of learners. Conclusion: The outcomes and evaluation results provide a foundation for improving the quality of similar future programs to ensure they are more well planned, better coordinated, and more professionally implemented.